Metabolizable energy intake of client‐owned adult cats. Issue 6 (12th October 2015) - Thes, M.; Koeber, N.; Fritz, J.; Wendel, F.; Dobenecker, B.; Kienzle, E.
Summary: A retrospective analysis of the metabolizable energy (ME) intake of privately owned pet cats from the authors' nutrition consultation practice (years 2007–2011) was carried out to test whether current recommendations are suitable for pet cats. Data of 80 adult cats (median age: 9.0 years, median deviation from ideal weight: +22.5%, majority neutered) at maintenance were available. Six percentage of the cats were healthy and the others were affected by various chronic diseases. A standardized questionnaire was used, cat owners weighed cat and food. For ration calculation, the software Diet Check Munich ™ was used (ME prediction according to National Research Council, 2006: Nutrient Requirements of Dogs and Cats . National Academy Press, Washington, DC). Data were analysed for the factors deviation from ideal weight, breed, age, gender, disease and type of feeding [prepared food (dry, wet) vs. home‐made]. Over‐ or underweight were defined as ≥15% deviation from ideal body weight (BW) according to Kienzle and Moik ( British Journal of Nutrition 2011, 106, Suppl 1: S113). Cat owner's estimation of ideal BW was higher than literature data from Kienzle and Moik (2011). Based on literature data, 26.3% of the pet cats were normal weight, 63.7% overweight and 10% underweight. The mean ME intake of all adult cats amounted to 0.40 ± 0.14 MJ/kg actual BW 0.67 ( n = 80). When the data were analysed according to normal, over‐ and underweight, there was a significant effect with normal weight cats eating 0.46 MJ/kg BW 0.67 . Underweight cats ate even more (0.49 MJ/kg BW 0.67 ), whereas overweight cats ate considerably less (0.36 MJ/kg BW 0.67 ). The other factors had no influence on ME intake of adult cats.